Parental Permissiveness And Family Functions On Unwanted Pregnancy In Teenagers - Septiarum, Rina; Suwarni, Linda; Alamsyah, Dedy (Unnes Journal of Public Health, 2019)
Abstract  ASFR (Age Specific Fertility Rate) in Sintang District of pregnancy on 15-19 years old teenagers was 9.85%, the highest in West Kalimantan. The aim of the study was to determine the association between parental permissiveness to teen dating behavior and the concept of family function with unwanted pregnancy in teenagers in the work area of Mensiku Health Center Sintang District. The study used a cross-sectional design with a quantitative approach. The sample in this study were 60 people. Statistical tests used the chi-square test with a confidence level of 95%. The results showed parental permissiveness (p-value = 0.004; PR = 2.176), religious function (p-value = 0.02; PR = 1.726), and reproductive function (p-value = 0.033; PR = 1.696) were associated with unwanted pregnancy. Social-cultural function, affection function, protection function, socialization and education function, economic function, environmental function were not associated with unwanted pregnancy (p value> 0.05). It was concluded that parental control, sex education, and the strengthening of religious education in the family environment were important factors associated to the incidence of unwanted pregnancy in teenagers.   Abstrak ASFR (Age Spesific Fertility Rate) di Kabupaten Sintang pada kehamilan 15-19 tahun sebanyak 9.85%, tertinggi di Kalimantan Barat. Tujuan penelitian untuk mengetahui hubungan antara permisifitas orang tua terhadap perilaku pacaran remaja dan konsep 8 fungsi keluarga dengan kehamilan tidak diinginkan pada remaja di wilayah kerja Puskesmas Mensiku Kabupaten Sintang. Penelitian menggunakan desain crosss sectional dengan pendekatan kuantitatif. Sampel dalam penelitian ini sebanyak 60 orang. Uji statistik menggunakan uji chi square dengan tingkat kepercayaan 95%. Hasil penelitian menunjukkan ada hubungan yang signifikan antara permisifitas orang tua (p value =0,004; PR=2,176), fungsi agama (p value=0,02; PR= 1,726), dan fungsi reproduksi (p value = 0,033; PR= 1,696) dengan kehamilan tidak diinginkan. Variabel yang tidak berhubungan yaitu fungsi sosial budaya, fungsi cinta kasih, fungsi perlindungan, fungsi sosialisasi dan pendidikan, fungsi ekonomi, fungsi lingkungan (p value > 0,05). Disimpulkan bahwa kontrol orang tua terhadap pergaulan anak remaja mereka, sex education, dan penguatan pendidikan agama di lingkungan keluarga menjadi faktor penting yang berkaitan dengan kejadian kehamilan tidak diinginkan pada remaja.